Effect of moisture content on physical properties of cashew nut of different varieties - Swami, Shrikant Baslingappa; A.M. Gawai, N.J. Thakor (Journal of Plantation Crops, 2016)
The physical properties, viz., geometric diameter, surface area, sphericity, volume, bulk density, true density and angle of repose was measured for four cashew varieties viz., Vengurle 1, Vengurle 3, Vengurle 4 and Vengurle 7 at different moisture content (15 to 87% db). For Vengurle 1 as the moisture content increased, the physical properties i.e., geometric mean diameter, volume, surface area, true density and angle of repose increased from 20.8 to 22.1 mm, 3485 to 4416 mm3, 1355 to 1540 mm2, 984 to 1030 kg m-3 and 32 to 37˚, respectively. The sphericity and bulk density decreased from 74.2 to 71.4 per cent and 490 to 418 kg m-3 respectively. For Vengurle 3 geometric mean diameter, volume, surface area, true density and angle of repose increased from 27.2 to 28.6 mm, 7912 to 9169 mm3, 2320 to 2567 mm2, 1020 to 1048 kg m-3 and 33 to 35.5˚, respectively. The sphericity and bulk density decreased from 75.5 to 75.2 per cent and 531 to 470 kg m-3 respectively. For Vengurle 4 the geometric mean diameter, volume, surface area, true density and angle of repose increased from 21.0 to 24.1mm, 3362 to 5113 mm3, 1391 to 1828 mm2, 970 to 1030 kg m-3 and 32.5 to 38˚, respectively. The sphericity and bulk density decreased from 65.8 to 66.8 per cent, 517 to 462 kg m-3, respectively. For Vengurle 7 the geometric mean diameter, volume, surface area, true density and angle of repose increased from 24.2 to 24.9 mm, 5102 to 5547 mm3, 1840 to 1941 mm2, 998 to 1045 kg m-3 and 33 to 38˚, respectively. The sphericity and bulk density decreased from 65.4 to 65.8 per cent, 518 to 438 kg m-3, respectively.